2008
DOI: 10.1088/1126-6708/2008/11/069
|View full text |Cite
|
Sign up to set email alerts
|

Quantum spinning strings in AdS4× ℂℙ3: testing the Bethe Ansatz proposal

Abstract: Recently, an asymptotic Bethe Ansatz that is claimed to describe anomalous dimensions of "long" operators in the planar N = 6 supersymmetric three-dimensional Chern-Simons-matter theory dual to quantum superstrings in AdS 4 × CP 3 was proposed. It initially passed a few consistency checks but subsequent direct comparison to one-loop string-theory computations created some controversy. Here we suggest a resolution by pointing out that, contrary to the initial assumption based on the algebraic curve consideratio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
154
2
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(167 citation statements)
references
References 62 publications
10
154
2
1
Order By: Relevance
“…There is yet another way to compute the one-loop shift directly from the world-sheet action which is similar to the algebraic curve computation. Whereas for the folded string both computations give the same excitation frequencies 15 , for the circular string a negative result was obtained in [109]. Recently it was shown that one should be more carefull with the periodicity of the fermionic fields in the world-sheet approach and the corrected derivation leads to agreement with the algebraic curve frequencies [110] so we assume all approaches to be consistent with each other.…”
Section: Non-symmetric Strong Coupling Solutionmentioning
confidence: 86%
See 1 more Smart Citation
“…There is yet another way to compute the one-loop shift directly from the world-sheet action which is similar to the algebraic curve computation. Whereas for the folded string both computations give the same excitation frequencies 15 , for the circular string a negative result was obtained in [109]. Recently it was shown that one should be more carefull with the periodicity of the fermionic fields in the world-sheet approach and the corrected derivation leads to agreement with the algebraic curve frequencies [110] so we assume all approaches to be consistent with each other.…”
Section: Non-symmetric Strong Coupling Solutionmentioning
confidence: 86%
“…At strong coupling the situation is less clear: in [75] and [78] the coefficient h 0 was argued to be 0 whereas in [109] some evidence was given in favor of a different value − log 2 2π (see also [74]). Hopefully this issue could be analyzed from world-sheet sigma model first principles calculation like in [79,80].…”
Section: Jhep06(2010)088mentioning
confidence: 99%
“…We note that there already exists evidence that the quantum corrections of the two theories are closely connected. 9 Indeed it was conjectured in [40], and tested for in [41,42,43,44], that the anomalous dimensions of twist operators of ABJM theory can be obtained from N = 4 super Yang-Mills, up to normalization factors which can be easily determined, simply by substituting,…”
Section: Discussionmentioning
confidence: 99%
“…However, in the three dimensional case there is still one player missing in the integrability game: the infamous function h(λ), mastering the dispersion relation of a single magnon moving on the spin chain [72][73][74]. Weak [75,76] and strong [77] coupling expressions have been obtained at leading and subleading orders, but no systematic method for computing h(λ) exists yet. On the other hand, it should be possible to find a three dimensional analogue of the set of TBA integral equations, used in [51,62], and apply it to the actual computation of B(λ), as done in [78,79].…”
Section: Jhep06(2014)123mentioning
confidence: 99%